Craniofacial Sleep Medicine: The Important Role of Dental Providers in Detecting and Treating Sleep Disordered Breathing in Children - Tammarie Heit; Bea Janine Tablizo; Martina Salud; Fan Mo; Mandip Kang; Mary Anne Tablizo; Manisha Witmans (MDPI AG, 2022)
Obstructive sleep apnea (OSA) is a clinical disorder within the spectrum of sleep-related breathing disorders (SRDB) which is used to describe abnormal breathing during sleep resulting in gas exchange abnormalities and/or sleep disruption. OSA is a highly prevalent disorder with associated sequelae across multiple physical domains, overlapping with other chronic diseases, affecting development in children as well as increased health care utilization. More precise and personalized approaches are required to treat the complex constellation of symptoms with its associated comorbidities since not all children are cured by surgery (removal of the adenoids and tonsils). Given that dentists manage the teeth throughout the lifespan and have an important understanding of the anatomy and physiology involved with the airway from a dental perspective, it seems reasonable that better understanding and management from their field will give the opportunity to provide better integrated and optimized outcomes for children affected by OSA. With the emergence of therapies such as mandibular advancement devices and maxillary expansion, etc., dentists can be involved in providing care for OSA along with sleep medicine doctors. Furthermore, the evolving role of myofunctional therapy may also be indicated as adjunctive therapy in the management of children with OSA. The objective of this article is to discuss the important role of dentists and the collaborative approach between dentists, allied dental professionals such as myofunctional therapists, and sleep medicine specialists for identifying and managing children with OSA. Prevention and anticipatory guidance will also be addressed.